The Phenomenon of Online Shopping Among the Cangkringmalang Village Community, Beji District, Pasuruan Regency During the Covid-19 Pandemic - Auria Eka Mayasari; Ruslianor Maika (Universitas Muhammadiyah Sidoarjo, 2021)
This study discusses two main issues of technological progress, the second issue is the trend of doing online shopping. Data were obtained through interviews with the Cangkringmalang village community, Beji sub-district, Pasuruan district using qualitative methods with a phenomenological perspective. In this study, primary data was collected using the Atlas.ti application to obtain efficient data. This study aims to find out how the phenomenon of online shopping among the public during the covid-19 pandemic. The conclusion is that the intensity of people's online shopping increases four to six times in a month, this is due to the Regulation of the Minister of Health regarding Large-Scale Social Restrictions in the context of Accelerating the Decline of the Covid-19 Virus. So that the impact of the regulation is limited space for informants.